Recent Advances in Hydrogenation Reactions Using Bimetallic Nanocatalysts: A Review. Issue 12 (12th November 2021) - Anand, Samika; Pinheiro, Dephan; Sunaja Devi, K. R.
Abstract: Hydrogenation reactions have been studied for many decades now and have developed from reactions that appear simple to now being recognized for their many complexities. These reactions are generally catalyzed using monometallic and more recently, with bimetallic nanocatalysts. Hydrogenation plays a vital role in food, chemical, petrochemical, pharmaceuticals, and dye industries to name a few. The hydrogenated products derived from several biomass‐based compounds are potential fossil fuels. Such products when employed in daily life, can help conserve natural resources. While hydrogenation of alkynes and alkenes are among the simplest of hydrogenation reactions, the most extensive and elegant manifestation of this reaction is seen in polymerization. Polymers like polythene, polypropylene (plastic) have replaced materials like glass, stainless steel, etc., in making daily use items for the obvious advantages of the former. Purification of alkenes is achieved by partially hydrogenating the respective alkynes present in trace amounts. This serves as an important step in the polymerization process. The presence of nitro group on aromatic rings makes them carcinogenic in nature which harms living organisms. For a safe environment, the elimination or modification of this nitro group becomes imperative. The products of hydrogenation of nitroaromatics and amino aromatics form the basis of pharmaceuticals and dyestuffs. A plethora of bimetallic catalysts have been used to catalyze these hydrogenation reactions. These catalysts are evaluated based on their selectivity and efficiency. This review highlights the recent advancements in the field of hydrogenation of nitro compounds, carbonyl compounds, and unsaturated hydrocarbons catalyzed by bimetallic nanoparticles. Abstract : The review is based on selective hydrogenation using bimetallic catalysts. It gives a detailed account of different methods used to prepare bimetallic nanocatalysts. It covers the hydrogenation of carbonyl compounds, including bio‐derived carbonyl compounds, cinnamaldehyde, citral, and the effect of catalysts on the yields and selectivity of the products obtained. The review includes previously discovered heterogeneous catalysts that are capable of partially hydrogenating alkynes to alkenes and nitroaromatic compounds to their respective amino compounds.